Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.jssc.2019.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surfactant on morphology, chemical properties and catalytic activity of hydroxyapatite

Abstract: Hydroxyapatite (HAP) was synthesised in the presence of surfactants and tested as a catalyst in CO oxidation. XRD confirmed that the characteristic HAP crystal phase was practically unaffected by the addition of surfactant. The surfactant altered both the Ca/P ratio and particle size of HAP. Catalyst tests showed that the activity of HAP increased for preparations using TWEEN, PEG and PVA. The temperature for 50% conversion, T50, values decreased from 340 °C for unmodified HAP, to 320 °C for TWEEN and to 315 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 39 publications
(41 reference statements)
1
14
0
Order By: Relevance
“…HAP can be synthesized by various methods, including sol-gel, wet precipitation, burning in the presence of microwaves and ultrasounds [14][15][16][17][18][19][20][21]. Its slightly alkaline pH and high biocompatibility will not cause any form of secondary environmental damage.…”
mentioning
confidence: 99%
“…HAP can be synthesized by various methods, including sol-gel, wet precipitation, burning in the presence of microwaves and ultrasounds [14][15][16][17][18][19][20][21]. Its slightly alkaline pH and high biocompatibility will not cause any form of secondary environmental damage.…”
mentioning
confidence: 99%
“…This means that the tested samples had, apart from recorded microporosity (pore size lower than 2 nm), also well-developed mesoporosity (pore size in the range of 2–50 nm). The isotherms presented in the figure allowed one to calculate the pore size distribution confirming their classification as the type IV [ 31 , 32 ]. Specific surface area of the samples amounted to 19.3 m 2 /g and 110.3 m 2 /g for nHAp and µHAp, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, hydroxyapatite particles with a Ca/P ratio of 1.7 were obtained to be a single phase by the hydrothermal method. It was considered that Ca-HAP(1.72) could be a solid solution resulting from the partial replacement of PO 4 3− ions with CO 3 2− ions [1,27]. In consequence, according to the XRD patterns, it was observed that single-phase hydroxyapatite particles were synthesized with a Ca/P molar ratio of 1.54-1.72.…”
Section: Characterizationmentioning
confidence: 99%
“…The stoichiometric form of Ca-HAP is shown as Ca 10 (PO 4 ) 6 (OH) 2 , and its Ca/P molar ratio is 1.67. However, while maintaining the single phase of apatite crystal structure, it is possible to change the Ca/P ratio ranging from 1.5 to 1.7 and substitute the constituents of Ca 2+ , PO 4 3− , and OH − with other elements to some extents [1]. Ca-HAP exhibits various unique properties, depending on changes in the chemical compositions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation